Design and development of a durian peeler : an ergonomics approach - Siti Norazila, Zahari (2010)
This study is to design a durian peeler machine that followed the ergonomic criteria.The problem statement for this study is workers who manually peeling durian can lead to MSD problem. Regarding the problem statement, the objective of this study is to design a durian peeler with an ergonomics approach using Solidworks software, develop a prototype of durian peeler machine and perfomed a simulation of the prototype. For the methodology, the design will be based on are data gathered from the literature review. The design based on the principles of ergonomics. The prototype of durian peeler develops using rapid prototyping process and simulates the prototype using ALGOR. For the result, a prototype is developed and simulation for the critical part of durian peeler. From the prototype of durian peeler, it showed some problem because of the process rapid prototyping that produce a solid design of prototype. For the validation of durian peeler, it involved working table and supporting bar. For the working table, the analysis of strength of material used in for the construction. Two different materials which are stainless steel AISI 304L AND steel ASTM A36. The stainless steel AISI 304L with higher shear modulus of elasticity is more suitable for the construction of durian peeler. For the supporting bar, the analysis of different forces had been applied. The forces that being applied shown that the ability of the working table to support the force. For the conclusion, the design of prototype of durian peeler using Solidwork had achieved. The prototype of durian peeler and simulation of durian peeler also been done.